(untitled) (Journal of the College of Languages (JCL), 2011)
The novel in its construction depends on set of life elements that is employed by the writer or the novelist to create a convincing world that resemble the real life world and as the novel is going toward experimentation and employing modern phenomenon we find the novelist tends to take advantage from the most realistic details to achieve the required convincing state through serious situations and the novelist Maysaloun Hadi depended in writing her novels on creating tight relations between the things and the elements that has inspired her which are mostly from the environment and from reality , as an example of these elements is the old inherited traditions that distinguish Iraq society as this element is a very important point in Iraq society especially for the public .So we find this element is the base that the novelist uses in constructing her novel Pharaon prophecy , for most situations were based on hiring this element . In her novel the Bride`s tea she also uses this element but lesser. The second element is the color which has taken a great place in her novels, the novelist depended on this element to deliver to us the symbols and signs that she wanted us to get. As the color is a very important and effective mean the novelist formed the situations according to it, in one time she uses it to show the psychological aspect, and in another time she hired this element to express the joy and happiness states or grief states. Although the color in the novel Pharaon prophecy has not have the same space that has been taken in the novel Bride`s tea but it represented an important psychological aspect through the use of intended symbols associated with the personalities` lives and the way and level of their living. The technique of Maysaloun`s Hadi novels depends on creating relations between the situations and making links between the elements and hire it successfully to represent a true image of the present living reality.